A formação emancipatória em Adorno e a primazia provisória da resistência sobre a adaptação no contexto educativo - Oliveira, Luana Aparecida de (2016)
This paper intends to present Adorno s conception of education and, from it, perform a critical confrontation with the current education. In the chapter entitled "Adorno s proposal for an emancipatory education and the assumptions necessary for such condition", we see that, for Theodor W. Adorno, education only makes sense when facing a formation that is emancipatory, to become the social place of non-identical theme and provide formative experiences able to contribute to the autonomous and critic development of individuals. Therefore, there are assumptions that, according to our author's reading, are conditions of possibility to occur the emancipatory process, and an important factor for this formation relates to the tension between adaptation and resistance. However, in the chapter: "Criticism of the current education from Adorno s philosophical fundamentals", the current education is analyzed and found that once it is located in a capitalist society, the set of its pedagogical practices reinforces largely the adaptation to the reality it faces. Thus, we can say that in this educational context the necessary tension to the emancipatory formation does not take place, since there is too much predominance of adaptation on resistance. From Adorno s theoretical reference, is part listed some elements that contribute to the unilateral strengthening of adaptive pole in formation, namely the barbarism through teaching through hardness, that is, by repression and fear, the instrumental reason and the cultural industry. All these factors result in the ideological model of semi-formation, namely the deformation of formation. Finally, on this issue, a possible alternative is developed in the chapter: "The provisional primacy of resistance in the educational context", where we argue that the educational sphere has the social commitment to prioritize resistance. Thus, the aim is to indicate the possibility of education to promote the various forms of resistance, so that, in this process, the purpose of emancipatory education can be strengthened.